Efectividad del programa educativo bebe sanito en el nivel de conocimiento de madres primigestas sobre cuidados al recién nacido 2012 - Sebastian Mendoza, Jenny Adela (2012)
This investigation study, of pre-experiment type, was realized in the centre of health “El Bosque”, during the months of June and July of the 2012, with the purpose of determining the educational program's effectiveness “Baby Sanita” in the knowledge level on lunch boxes in mothers and/or people who take care of preschool students with nutrition problems. The sample was constituted of 25 mothers primiparous who obeyed the inclusion criteria mentioned in the investigation. To obtain the data we used the instrument: Rank of Knowledge on care of the newborn (RKCNB), being the obtained information processed and analyzed by: The statistical test for correlated data “t de student”, the results are presented in simple tables, double entrance tables and graphics. The following conclusions were reached after the analysis:Before the application of the educational program, the 68 percent of mothers primiparous got a regular knowledge level,after the educational program's application, the majority of mothers primiparous got a good- knowledge level 84 percent and the educational program was effective to the improving the knowledge level of mothers primiparous about baby care, (p=0.000).